TINJAUAN KASUS PENCEMARAN NAMA BAIK BERDASARKAN KUHP YANG BERKEPASTIAN HUKUM - Angelina, Jennifer; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: Articles 310–316 of the Criminal Code address the offense of defamation of reputation, with the goal of safeguarding individuals' honor and dignity. The standards for what is considered damage to one's reputation require reevaluation with regard to numerous aspects. The public's hazy understanding of defamation further highlights the importance of having precise legal guidance. Reviewing pertinent statutes and court records is an integral part of the normative law research methodology. The ruling by the Constitutional Court in Decision No. 78/PUU-XXI/2023 states that the defamation Criminal Code Article 310 Paragraph 1 is deemed "conditionally unconstitutional" due to its incompatibility with the principles outlined in the 1945 Constitution. That is why Law No. 1 of 2023 will amend Article 310 of the Criminal Code to Article 433 in order to close the gap, make discrimination less likely, and avoid ambiguity in its application. Legal action cannot be pursued without an official report from the party who feels wronged by the action, as stated in Article 310 of the Criminal Code (KUHP) and Decision No. 78/PUU-2023 of the Constitutional Court, as well as Article 433 of Regulation No. 1 Year 2023. So, when it comes to defamation charges, law enforcement needs to be extra careful and not make hasty decisions without taking everything into account.Keywords: Policy, Criminal Law, Defamation.